Functional Food Components, Intestinal Permeability and Inflammatory Markers in Patients with Inflammatory Bowel Disease - Lacerda, Joana Franco (Nutrients, 2021)
Inflammatory bowel diseases (IBD) are characterized by a chronic inflammatory process that affects the intestinal barrier structure. Recent evidence suggests that some food components can influence the integrity of the intestinal barrier and thus its permeability. We aimed at assessing the effect of food components on the intestinal permeability (IP) and on inflammatory markers in individuals with IBD by a single-blind randomized clinical study. Of the 53 individuals included, 47% (n = 25) had been diagnosed with IBD. The participants were divided into 4 groups. IBD patients were allocated to intervention group (n = 14) vs. no intervention group (n = 11), and the same happened with 28 control participants without disease (n = 14 in intervention group vs. n = 14 without intervention). Symptomatology, nutritional status, biochemical parameters (specifically serum zonulin (ZO) to measure IP) were evaluated on all individuals on an eight week period following a diet plan with/without potentially beneficial foods for the IP. At the beginning of the study, there were no significant differences in ZO values between individuals with and without IBD (p > 0.05). The effect of specific food components was inconclusive; however, a trend in the reduction of inflammatory parameters and on the prevalence of gastrointestinal symptomatology was observed. More controlled intervention studies with diet plans, including food components potentially beneficial for the integrity of the intestinal barrier, are of the utmost importance.